2022
DOI: 10.1038/s41598-022-19770-9
|View full text |Cite
|
Sign up to set email alerts
|

A radiomics-based study for differentiating parasellar cavernous hemangiomas from meningiomas

Abstract: To investigate the value of the radiomic models for differentiating parasellar cavernous hemangiomas from meningiomas and to compare the classification performance with different MR sequences and classifiers. A total of 96 patients with parasellar tumors (40 cavernous hemangiomas and 56 meningiomas) were enrolled in this retrospective multiple-center study. Univariate and multivariate analyses were performed to identify the clinical factors and semantic features of MRI scans. Radiomics features were extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…However, Wang et al recently reported that the application of a radiomics-based algorithm using diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) facilitates the distinction of meningiomas from cavernous malformations. 19 Future automated radiomics may assist in the preoperative distinction, which may have implications for treatment evaluation, such as additional angiographic imaging for larger lesions. In single-photon emission computed tomography (SPECT), cavernous malformations are usually low in uptake, whereas in other tumors such as meningiomas, the metabolic uptake may be higher.…”
Section: Discussionmentioning
confidence: 99%
“…However, Wang et al recently reported that the application of a radiomics-based algorithm using diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) facilitates the distinction of meningiomas from cavernous malformations. 19 Future automated radiomics may assist in the preoperative distinction, which may have implications for treatment evaluation, such as additional angiographic imaging for larger lesions. In single-photon emission computed tomography (SPECT), cavernous malformations are usually low in uptake, whereas in other tumors such as meningiomas, the metabolic uptake may be higher.…”
Section: Discussionmentioning
confidence: 99%
“…From prior meningioma grading studies, it is known that multilevel feature selection can give better results. Fifteen feature selection methods were selected based on previous related research [13,31,[33][34][35][36], including the filter methods Chi-square (CHSQ), t-test (TSQ), Kruskal-Wallis H-test tests (KWH), variance (VAR), relief (RELF), mutual information (MI), minimum redundancy maximum relevance ensemble (mRMRe) and the embedded methods L1-based logistic regression (L1-LR), elastic net (EN), least absolute shrinkage and selection operator (LASSO), L1-based linear support vector machine (L1-SVM), random forest (RF), extra tree ensemble (ETE), gradient boosting decision tree (GBDT), and xgboost (XGB). In this study, the filter methods were used as the first level of screening to reduce the number of features, and the embedded methods were used as the second level of screening to obtain the final features.…”
Section: Feature Selection Methodsmentioning
confidence: 99%
“…The field of radiomics is another area where AI is making significant strides. By extracting quantitative features from radiographic images, machine learning algorithms are enhancing the diagnosis of rare neurological diseases and tumors [61][62][63]. These models not only compete with but, in some cases, outperform human experts in diagnosing conditions like high-grade gliomas [64,65].…”
Section: Diagnosismentioning
confidence: 99%